Managing female athlete health: Auditing the representation of female versus male participants among research in supplements to manage diagnosed micronutrient issues - Smith, E. S.; McKay, A. K. A.; Kuikman, M.; Ackerman, K. E.; Harris, R.; Elliott-Sale, K. J.; Stellingwerff, T.; Burke, L. M. (Nutrients, 2022)
Micronutrient deficiencies and sub-optimal intakes among female athletes are a concern and are commonly prevented or treated with medical supplements. However, it is unclear how well women have been considered in the research underpinning current supplementation practices. We conducted an audit of the literature supporting the use of calcium, iron, and vitamin D. Of the 299 studies, including 25,171 participants, the majority (71%) of participants were women. Studies with exclusively female cohorts (37%) were also more prevalent than those examining males in isolation (31%). However, study designs considering divergent responses between sexes were sparse, accounting for 7% of the literature. Moreover, despite the abundance of female participants, the quality and quantity of the literature specific to female athletes was poor. Just 32% of studies including women defined menstrual status, while none implemented best-practice methodologies regarding ovarian hormonal control. Additionally, only 10% of studies included highly trained female athletes. Investigations of calcium supplementation were particularly lacking, with just two studies conducted in highly trained women. New research should focus on high-quality investigations specific to female athletes, alongside evaluating sex-based differences in the response to calcium, iron, and vitamin D, thus ensuring the specific needs of women have been considered in current protocols involving medical supplements.